Trade Credit and Taxes - Desai, Mihir A.; Foley, C. Fritz; Hines, James R. (The Review of Economics and Statistics, 2016)
This paper analyzes the extent to which tax differences affect the use of trade credit. U.S.-owned affiliates in low-tax countries use trade credit to lend, whereas those in high-tax countries use trade credit to borrow: 10% lower local tax rates are associated with net trade credit positions that are 1.4% higher as a fraction of sales. The use of trade credit to get capital out of low-tax, low-return environments is also illustrated by the temporary repatriation tax holiday in 2005, which was used most intensively by affiliates with positive net trade credit positions.